Teduglutide treatment during breast feeding in a patient with intestinal failure: a case report - Lillienau, Jan; Nilsson, Elin; Vulcan, Alexandra; Nilsson, Åke (Frontiers in Nutrition, 2025)
Successful pregnancy and breast feeding during intravenous treatment for advanced intestinal failure (IF) is possible with careful surveillance and appropriate adjustment of the nutritional regimen. However, experience of GLP-2 agonists in this context is lacking. Here we describe a patient with IF who underwent two successful pregnancies and who used teduglutide during breastfeeding after the second pregnancy, with good effect and without negative side effects.